2013
DOI: 10.3892/mmr.2013.1417
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide prevents H2O2-induced senescence in human umbilical vein endothelial cells through SIRT1 activation

Abstract: The aim of the present study was to investigate the attenuation of endothelial cell senescence by H2S and to explore the mechanisms underlying the anti-aging effects of H2S. Senescence was induced in human umbilical vein endothelial cells (HUVECs) by incubation in 25 µmol/l H2O2 for 1 h. Senescence-associated β-galactosidase (SA-β-gal) activity was examined to determine the effects of H2S on senescent HUVECs. The results indicated that SA-β-gal activity in the H2O2-treated HUVECs was 11.2 ± 1.06%, which was at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 36 publications
6
57
0
Order By: Relevance
“…H 2 O 2 is a common reactive oxygen species that promotes free radical generation, which is able to enter and accumulate within cells, resulting in cellular damage (10). The reported concentrations of H 2 O 2 required to induce cell lesions varies widely in the literature (11)(12)(13). In the present study, 500 mmol/l H 2 O 2 was used, and the results showed that ~10% of the cells were in the DNA synthesis (S) or mitotic (G 2 ) phase of the cell cycle.…”
Section: Discussionmentioning
confidence: 65%
“…H 2 O 2 is a common reactive oxygen species that promotes free radical generation, which is able to enter and accumulate within cells, resulting in cellular damage (10). The reported concentrations of H 2 O 2 required to induce cell lesions varies widely in the literature (11)(12)(13). In the present study, 500 mmol/l H 2 O 2 was used, and the results showed that ~10% of the cells were in the DNA synthesis (S) or mitotic (G 2 ) phase of the cell cycle.…”
Section: Discussionmentioning
confidence: 65%
“…Recent studies demonstrated that senescence can be induced in many cell types under various conditions and treatments such as hypoxia, uremia, UVB, radiation, H 2 O 2 and oxidized low-density lipoprotein (59)(60)(61)(62)(63)(64). Previous studies indicated that β-galactosidase activity is a major characteristic found in senescence cells and is generally applied to senescence detection (65)(66)(67).…”
Section: Discussionmentioning
confidence: 99%
“…NaHS treatment results in the upregulation of both XOD and p67 (phox) levels but down-regulation of Mn-SOD expression [116], thereby slowing down cell aging. Another study shows that H 2 S delays HUVEC senescence and prevents H 2 O 2 -induced damage via sirtuin 1 activation [125]. In addition, H 2 Sreleasing drugs, NaHS and ACS6 (both at 10 µM), inhibit superoxide formation and gp91 (phox) (a catalytic subunit of NADPH oxidase) expression in porcine pulmonary arterial ECs by increasing cAMP levels and recruiting PKA upon the inhibition of PDE-5 [126].…”
Section: The Roles Of H 2 S and No In Oxidative Stressmentioning
confidence: 99%
“…4), whereas NaHS pretreatment reverses the changes in SOD activity and H 2 O 2 level [116]. Similarly, the expression levels of both xanthine oxidase (XOD) and subunits p67 (phox) of NADPH oxidase are increased in the senescent group relative to the fresh one, whereas manganese-superoxide dismutase (Mn-SOD) expression levels are decreased [125]. NaHS treatment results in the upregulation of both XOD and p67 (phox) levels but down-regulation of Mn-SOD expression [116], thereby slowing down cell aging.…”
Section: The Roles Of H 2 S and No In Oxidative Stressmentioning
confidence: 99%